An Extended Grendel Approach Applied to Blockchain Signature as an Alternative to Keccak Permutation - ABDELKARIM LKOAIZA; Seddik ABDELALIM; Asmaa CHERKAOUI; Ilias ELMOUKI (Statistics, Optimization & Information Computing, 2025)
In this paper, we present our own developed programming which helps to generate a sponge-based function while avoiding any call from hashing libraries. Then, we try to implement it in a blockchain signature by getting inspired from Keccak methods such as the recently inextinguishable Secure Hash Algorithm 3 (SHA-3), but before this, we note that our main contribution here, is about introducing the Grendel permutation instead of the Keccak one as they both rely on sponge-based procedures, but the shuffling step is different. In fact, even our Legendre symbol considered here, extends the Euler criterion that is restricted to prime field, to the cases of the group of invertible elements Z/pqZ. To the best of our knowledge, this is the first time that such an approach is used in blockchain signature.